(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Around the world, the utilization of concrete is increasing significantly. Due to the gradual increase in material waste caused by population growth and urbanization, research into the use of waste building materials is important. The key objective of this study is to examine how concrete behaves and how its characteristics alter when waste glass and waste plastic aggregate are used instead of natural aggregates. Solid waste management is one of the most significant environmental issues facing by the world today. The best material for recycling is glass. Therefore, using waste glass as a substitute for fine aggregate in concrete is an interesting possibility in terms of the economy of waste landfills and the conservation of natural resources. Safe disposal of plastic waste is an important environmental problem that needs to be mitigated. From this point of view, this investigation is an attempt to evaluate whether it is appropriate to use waste glass and waste plastic as a substitute for fine and coarse aggregate, which helps in the production of light-weight concrete. M60-grade concrete is used in this study. M60-grade concrete is used for reinforced concrete structures (RCC) in high-rise buildings, long-span bridges, and other structures that require high compressive strength. The construction of decisive environmental systems takes advantage of this. The spillways of dams are also constructed with M60-grade concrete. For M60 grade concrete, the fine aggregate is replaced with waste glass and the coarse aggregate is replaced with waste plastic aggregate, and the compressive strength test is conducted. The percentage by weight of waste glass with fine aggregate is 0% and 10% and waste plastic with coarse aggregate is 0%, 5%, 10%, 15%, 20%, 25%, 30% and 35%, respectively.